Rock Stability Assessment Based on the Chronological Order of the Characteristic Acoustic Emission Phenomena - Penghai Zhang; Tianhong Yang; Tao Xu; Qinglei Yu; Jingren Zhou; Wancheng Zhu (Shock and Vibration)
Sudden inelastic deformations in rock are associated with acoustic emission (AE). Therefore, AE monitoring technique can be used to study the fracture processes of rock. In this paper, AE tests were conducted on the granitic gneiss specimens under the uniaxial compressive loading conditions. The temporal changes in AE hit parameters and spatial-temporal evolution of AE events during the failure process of the granitic gneiss specimens were studied, and several characteristic AE phenomena (i.e., dramatic increase in dominant frequency, AE energy, and hit rate, the AE event with a high energy level, and the through-going distribution of the AE events with intermediate energy levels) were statistically analyzed before the failure occurred. It was found that the chronological order of the characteristic AE phenomena was relatively certain and correspondingly had a close relationship with the crack development stage. Because of the difference of the stress level at each crack development stage, the stability at different crack development stages is different. Therefore, a rock stability assessment approach was established based on the chronological order of the characteristic AE phenomena, and then the rock stability was assessed using the proposed approach.